2013
DOI: 10.1186/1746-4358-8-10
|View full text |Cite
|
Sign up to set email alerts
|

Trends in infant and young child feeding practices in Bangladesh, 1993–2011

Abstract: BackgroundOptimal infant and young child feeding practices are crucial to improving the health and nutritional status of children. Bangladesh Breastfeeding Foundation, UNICEF and several other organizations are working in the country for the promotion of healthy feeding practices. This article presents trends in breastfeeding and complementary feeding practices in Bangladesh from 1993–2011, based on data in Bangladesh Demographic and Health Surveys. The following Bangladesh Demographic and Health Surveys were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 1 publication
0
9
1
Order By: Relevance
“…Dietary diversity was explored in 11 studies [6,8,[13][14][15][16][17][18][19][20][21], with 4 using the seven WHO IYCF food groups to quantify MDD [14][15][16]19]. Their data suggests a declining trend in MDD achievement between 2007 and 2011, with current attainment around 25%.…”
Section: Minimum Dietary Diversitymentioning
confidence: 99%
See 2 more Smart Citations
“…Dietary diversity was explored in 11 studies [6,8,[13][14][15][16][17][18][19][20][21], with 4 using the seven WHO IYCF food groups to quantify MDD [14][15][16]19]. Their data suggests a declining trend in MDD achievement between 2007 and 2011, with current attainment around 25%.…”
Section: Minimum Dietary Diversitymentioning
confidence: 99%
“…The 2007 BDHS combined groups M and E into a single "meat, fish, and eggs" group; this figure may therefore underestimate the true value. In the 2011 BDHS the reported rate had fallen to 25% [19]. A large cohort study conducted in rural subdistricts in 2011 provides an even lower number; Owais et al (Weight of Evidence = High (WOE = H)) interviewed 2073 mother-child pairs over 9 months, and found that just 16% of children received the necessary four food groups per day to satisfy MDD [15].…”
Section: Minimum Dietary Diversitymentioning
confidence: 99%
See 1 more Smart Citation
“…Early initiation of breastfeeding (within an hour of birth) is also recommended by WHO [9] and delayed initiation has been associated with increased risk of infant mortality [1014]. However, despite exclusive breastfeeding advocacy efforts and evidence that breastfeeding improves infant outcomes in Bangladesh [15], early and exclusive breastfeeding remains low [1618]. A comprehensive study found a 47.1% prevalence of early breastfeeding and 64.1% prevalence of exclusive breastfeeding until six months in 2011 in Bangladesh [16].…”
Section: Introductionmentioning
confidence: 99%
“…However, despite exclusive breastfeeding advocacy efforts and evidence that breastfeeding improves infant outcomes in Bangladesh [15], early and exclusive breastfeeding remains low [1618]. A comprehensive study found a 47.1% prevalence of early breastfeeding and 64.1% prevalence of exclusive breastfeeding until six months in 2011 in Bangladesh [16]. Additionally, early complementary feeding continues to occur [19, 20].…”
Section: Introductionmentioning
confidence: 99%